Rejection of blood donors in a Peruvian hospital during the COVID-19 pandemic - Nelly Alondra Sanchez Saravia; Marian Mendoza Castillón; Jhosmar Vilca Herrera; Ángel Rodríguez Quispe (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: SARS-CoV-2 has had a negative and significant impact on global health systems, threatening the necessary blood supply for clinical transfusions. Objective: To describe the causes of rejection of blood donors during the COVID-19 pandemic. Methods: An observational, cross-sectional and retrospective study was carried out in a population of donors who attended the Blood Bank of Ramiro Prialé Prialé National Hospital, in Huancayo, Peru, from July, 2020 to the same month, 2022. The analyzed variables were sex, the ABO blood group, Rh factor and types and causes of rejection. Results: Of total of 10 177 blood donors, 3390 (33.3%) were differed and excluded; the most frequent cause of differing was the low hematocrit (18.0%) and the most frequent cause of exclusion was antibody to hepatitis B core antigen positivity (36.8%). Likewise, male sex predominated among those who were rejected (55.2%) and an increment of the polytomous tendency was evidenced in differed (R²=0.2214) and excluded donors (R²=0.1178). Conclusions: The prevalence of differing and exclusion in blood donors was relatively high compared to that reported in other studies, which was mainly due, in each respective case, to the low hematocrit and the presence of antibody to hepatitis B core antigen.